Retrospective Analysis of Postchemotheraphy Retroperitoneal Lymph Node Dissection (PC-RPLND) Results in Patients with Non-Seminomatous Testicular Cancers - Hasan Soydan; Ercan Malkoç; Sezgin Okçelik; Ömer Yılmaz; Ferhat Ateş; Furkan Dursun; Kenan Karademir; Temuçin Şenkul1 (Journal of Urological Surgery, 2015)
Objective Resection of residual masses after chemoteraphy in patients with nonseminomatous testicular cancer is recommended. In our study, we evaluated the patients’ data underwent post chemotherapy retroperitoneal lymph node dissection (PC-RPLND). Materials and Methods Patients with advanced staged tumors and Non-seminomatous germ cells and having residual mass after chemotherapy whose tumor markers returned to normal were selected in the study. Pre-chemotherapy mass size, postchemoterapy mass size, decrease rate in the mass size, prognostic factors of local tumor, International Germ Cell Collaborative Clasification (IGCCC) risk groups, and teratoma existence in primary pathology, PC-RPLND pathologies were compared for fibrozis, teratoma or viable tumor presence. In addition, patients with and without intraoperative complications were compared in terms of the same parameters. Comparisons were conducted using Statistical Packages for the Social Sciences (SPSS) 16.0 and p<0.05 was considered statistically significantResults Twenty six patients were included in the study. Respectively 4 (15%) viable tumors, 14 (54%) teratoma, 8 (31%) necrosis were observed in patients after PC-RPLND. No significant differences were observed in PC-RPLND pathology results in IGCCC risk groups depending on presence of teratoma in primary tumor or existence of more than 50% embryonal carcinoma after orchiectomy pathology. Teratoma in 6 of 8 patients with no decrease in the mass rate and viable tumor in 2 patients were detected. More than 90% reduction rate in the mass was detected in only one patient whose PC-RPLND pathology result was necrosis.There were no significant variations between complication developed and undeveloped patients in terms of mass size and live tumor existence. Conclusion Our data is consistent with the current literature. The mass size decrease rate, teratoma presence in orchiectomy material, IGCCC risk groups and local prognostic factors are not accurate predictive factors in determining the PCRPLND pathology